A comprehensive review of different electric motors for electric vehicles application - Krishnamoorthy, Sreeram; Panikkar, Preetha Parakkat Kesava (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Electric vehicles (EVs) offer several advantages over internal combustion engines (ICE), including high energy efficiency, noise reduction, low maintenance, and a wider speed range. This results in lower fuel consumption, reducing dependency on oil imports and enhancing energy security. The motor drive is a critical component of EVs, providing the necessary propulsion force. This paper presents a comprehensive comparison of state-of-the-art motors suitable for EV applications, including DC motors, induction motors (IM), brushless DC motors (BLDC), permanent magnet synchronous motors (PMSM), and switched reluctance motors (SRM). Various design aspects relevant to traction applications, such as cost, reliability, efficiency, torque, fault-tolerance ability, excitation arrangements, and power density are also addressed. The performance of an EV based on the SRM drive is analyzed using MATLAB Simulink, with a special focus on parameters like speed, torque, flux, and state of charge (SOC). The review highlights that SRM drives have significant potential in EVs due to their reliable structure, fault tolerance capability, and magnet-free design. However, their application in EVs is currently limited due to torque ripples, as evident from the simulations. This paper is expected to serve as a foundation for further enhancing the performance of SRM drives for EV applications.